From Shared Enaction to Intrinsic Value. How Enactivism Contributes to Environmental Ethics. - Werner, Konrad; Kiełkowicz-Werner, Magdalena (Topoi: An International Review of Philosophy, 2022)
Two major philosophical movements have sought to fundamentally rethink the relationship between humans and their environment(s): environmental ethics and enactivism. Surprisingly, they virtually never refer to or seek inspiration from each other. The goal of this analysis is to bridge the gap. Our main purpose, then, is to address, from the enactivist angle, the conceptual backbone of environmental ethics, namely the concept of intrinsic value. We argue that intrinsic value does indeed exist, yet its "intrinsicality" does not boil down to being independent of the interests and needs of humans. Rather, it is brought forth by what we call shared enaction of an axiological domain. The latter is built upon such core posits of enactivism as autonomy, enaction, participatory sense-making as well as the most recent concept of loving as knowing proposed by Hanne De Jaegher.